Underwater and Surface Swimming Parameters Reflect Performance Level in Elite Swimmers - Pla, Robin; Poszalczyk, Gauthier; Souaissia, Cyrine; Joulia, Fabrice; Guimard, Alexandre (Frontiers in Physiology, 2021)
Although the role of underwater phases is well known, no study has taken an interest in describing and quantifying the distance and time spent in apnea as a condition for an optimal performance. The aim of this study is to investigate the impact of time and distance spent underwater and surface parameters on the swimming performance in elite swimmers. The performances of 79 swimmers in 100-m freestyle were analyzed (short-course). The underwater and spatio-temporal parameters of three groups have been recorded: 2018 world finalists (WORLD), french swimmers who reached a 100m performance time under 50s at 2018 french national championships (UND50) and those who reached a 100m performance time above 50s (UP50). WORLD spent more distance underwater (37.50 ± 4.92m) than UND50 (31.90 ± 4.88m, p<0.05) and UP50 (31.94 ± 4.93m, p<0.01). The total percentage of underwater time was higher for WORLD (39.11 ± 4.73%) versus UND50 (34.21 ± 4.55%, p<0.05) and UP50 (33.94 ± 5.00%, p<0.01). Also, underwater speed was higher for WORLD (2.54 ± 0.05 m/s) compared with UND50 (2.46 ± 0.09 m/s, p<0.05) and UP50 (2.38 ± 0.11 m/s, p<0.01). The key results of the 100-m freestyle match the underwater phases as: distance underwater, speed underwater and total percentage of underwater time. These data suggest an appropriate focus on a specific apnea training to improve underwater skills during short-course swimming performances.